Reducing the Consequences of Accidental Fires in Oil & Gas Facilities: a Risk-Based Procedure for Identification of the Fireproofing Zones - A. Tugnoli (Chemical Engineering Transactions, 2013)
Accidental fires in Oil&Gas facilities have a significant potential for severe consequences, endangering personnel safety, environment, asset integrity, production continuity and company reputation. Moreover, in-plant accident propagation (domino effects) may further increase the outcomes of fires. Fireproofing is a crucial safety barrier in preventing the escalation of fire scenarios. Maintenance and cost considerations require the application of such protection only where an actual risk of severe fire scenarios is present. Available methodologies for the identification of fireproofing zones in on-shore installations are based on simplified assumptions and do not consider the effect of jet-fire scenarios. Experience has tragically shown though the importance of including such scenarios (e.g. Valero accident in 2007). In the present study, a risk-based methodology for the identification of fireproofing zones was developed. The procedure addresses both the prevention of domino effect and the mitigation of asset damage due to the primary fire scenario (pool and jet fires), taking into account the specific issues of on-shore applications. Specific criteria were introduced to assess escalation hazard. A risk-based identification of the reference accident scenarios was developed, allowing a more detailed definition of the plant items that should be considered for fireproofing application. The method is mainly oriented to early design application, allowing the identification of fireproofing zones in the initial lay-out definition. The potential outcomes of the methodology are investigated by applying them to case-studies of industrial interest.